Combination of apolipoprotein-A-I/apolipoprotein-A-I binding protein and anti-VEGF treatment overcomes anti-VEGF resistance in choroidal neovascularization in mice - Zhu, Lingping; Parker, Mackenzie; Enemchukwu, Nduka; Shen, Megan; Zhang, Guogang; Yan, Qing; Handa, James T.; Fang, Longhou; Fu, Yingbin (Communications biology, 2020)
Many patients of choroidal neovascularization (CNV) are unresponsive to the current anti-VEGF treatment. The mechanisms for anti-VEGF resistance are poorly understood. We explore the unique property of the apolipoprotein A-I (apoA-I) binding protein (AIBP) that enhances cholesterol efflux from endothelial cells and macrophages to thereby limit angiogenesis and inflammation to tackle anti-VEGF resistance in CNV. We show that laser-induced CNV in mice with increased age showed increased resistance to anti-VEGF treatment, which correlates with increased lipid accumulation in macrophages. The combination of AIBP/apoA-I and anti-VEGF treatment overcomes anti-VEGF resistance and effectively suppresses CNV. Furthermore, macrophage depletion in old mice restores CNV sensitivity to anti-VEGF treatment and blunts the synergistic effect of combination therapy. These results suggest that cholesterol-laden macrophages play a critical role in inducing anti-VEGF resistance in CNV. Combination therapy by neutralizing VEGF and enhancing cholesterol removal from macrophages is a promising strategy to combat anti-VEGF resistance in CNV. By combining advanced age and laser photocoagulation, Zhu et al. establish a novel CNV model of anti-VEGF resistance. They show that lipid accumulation in old macrophages promote angiogenesis, and that apoA-I binding protein (AIBP) inhibits angiogenesis by reducing this lipid accumulation. They further show that the combination of AIBP/apoA-I and anti-VEGF treatment overcomes anti-VEGF resistance and effectively suppresses CNV.